Kajian Progresif Transforming Gender Equality Initiatives: Evaluating Strategic Solutions and Institutional Challenges in International Legal Resolution and Islamic Law, Gay, Biseksual, Transgender Dalam Konsep Hukum Gender Internasional dan Hukum Islam - Iffan, Ahmad; Mustafid; Arizal, Hendriko; Chandra SYd, Helmi; Faiz Algifari, Muhammad; Pradana, Syafa'at Anugrah (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This study examines the intersection of gender, human rights, and international law, with a focus on the influence of gender perspectives on international legal frameworks and human rights practices. Utilizing a qualitative, literature-based methodology, the research analyzes existing legal documents, scholarly articles, and international treaties to evaluate how gender considerations impact human rights enforcement and legal interpretations. The findings reveal that incorporating gender perspectives into international law can enhance the effectiveness of human rights protections and address gender-specific injustices more comprehensively. The originality of this research lies in its critical examination of how gender dimensions are integrated into legal practices and the impact of these integrations on global human rights standards. The study's implications emphasize the need for ongoing reforms in international law to better address gender inequalities and promote more equitable human rights protections. These two conceptions can be a solution to various gender problems in national law.